Monitoring of Marine Biofilm Formation Dynamics at Submerged Solid Surfaces With Multitechnique Sensors - Grzegorczyk, Maciej; Pogorzelski, Stanisław Józef; Pospiech, Aneta; Boniewicz-Szmyt, Katarzyna (Frontiers in Marine Science, 2018)
Biofouling on artificial and biotic solid substrata was studied in several locations in the Baltic Sea brackish water (Gulf of Gdansk) during a three-year period with contact angle wettability, confocal microscopy and photoacoustic spectroscopy techniques. As a reference, the trophic state of water body was determined from chemical analyses according to the following parameters: pH, dissolved O2, phosphate, nitrite, nitrate, ammonium etc. concentrations and further correlated to the determined biofilm characterizing parameters by means of Spearman’s rank correlation procedure. Biofilm adhesive surface properties (surface free energy, work of adhesion etc.) were obtained with the contact angle hysteresis (CAH) approach using an automatic captive bubble solid surface wettability sensor assigned for in-situ, on-line and quasi-continuous measurements of permanently submerged samples (Pogorzelski et al., 2013, Pogorzelski and Szczepańska, 2014). Structural and morphological biofilm features (biovolume, substratum coverage, area to volume ratio, spatial spreading, mean thickness and roughness) were determined from confocal reflection microscopy (COCRM) data. Photosynthetic properties (photosynthetic energy storage (ES), photoacoustic amplitude and phase spectra) of biofilm communities exhibited a seasonal variability as indicated by a novel closed-cell type photoacoustic spectroscopy (PAS) system. That allowed mathematical modeling of a marine biofilm under steady state, in particular the specific growth rates μi, and the conditioning or induction times λi to be derived from simultaneous multitechnique signals. A set of the established biofilm structural and physical parameters could be modern water body trophic state indexes.